A Contactless Planar Inductive Sensor for Absolute Angular Displacement Measurement - Wenzheng Gao; Hong Shi; Qifu Tang (IEEE Access, 2021)
This paper proposes a new planar inductive sensor with printed circuit boards (PCB) based stator and rotor, which can perform more precision measurement than traditional inductive angular displacement sensors. The sensor uses PCB technique to realize accurately configured planar coils. The stator consists of a ferromagnetic base plate and a PCB with three groups of circular excitation coils and two groups of sine shape pickup coils working as two sense channels. The rotor consists of a ferromagnetic base plate and a PCB with two circles of copper pieces. Copper pieces on the rotor PCB produce eddy current in the time-varying magnetic field and alter the outputs of two sense channels of pickup coils cyclically with the rotor’s rotation. Two sense channels can make incremental angle measurement individually and work together to make absolute angle measurement. A prototype with 63 and 64 period sense channels was designed and developed for experiments, and test results show that it was finally examined with short-period error of $14.7^{′ ′ }$ and full range error of $20.6^{′ ′ }$ . The possessed characteristics of inductive principle, absolute measuring and good accuracy make this type of sensor is very suitable for high precision, reliable measurement in harsh environments.